E-Commerce Business Strategy Creative Clothing Industry In Kuta Region In The New Normal Era - I Kadek Yudha Cahaya Pekasa; I Gede Sanica (Eduvest - Journal of Universal Studies, 2021)
The purpose of this study is to determine Huck's business strategy in the marketplace to face the new normal era in preparing and implementing the strategy. The type of data used in this study is data collection through interviews and observation. The data That have been collected analyzed using an triangulation model data analysis. The results of data analysis obtained by Huck's business strategy to build an online store in the marketplace using an e-marketing strategy which is divided into product and service, price, placement and distribution, promotion, and people. The purpose of using this strategy is to find out the accuracy in choosing strategies in online marketplace stores and get sales targets through online stores in the midst of the Covid-19 pandemic. The strategy that has been implemented for a year has resulted in 100 total product sales and received the star seller title in marketplace also getting chat performance of 44%.